Design of Micro Size Optical Scanner Systems - Samira M. Arif; Mohamed S. Ahmed; Dayah N. Raouf (Engineering and Technology Journal, 2012)
The design and analysis of micro optical scanner systems are presented. A simulate software was implemented to study, firstly, the effects of miniaturization on the general optical properties of the system, secondly, the optical design and performance characteristics for two specific micro scanner models. These are single aperture scanner and a focal Keplerian telescopic systems, taking in consideration the performance requirements of these systems for various medical applications.